2007
DOI: 10.1890/06-1512
|View full text |Cite
|
Sign up to set email alerts
|

Functional Responses: A Question of Alternative Prey and Predator Density

Abstract: Abstract. Throughout the study of ecology, there has been a growing realization that indirect effects among species cause complexity in food webs. Understanding and predicting the behavior of ecosystems consequently depends on our ability to identify indirect effects and their mechanisms. The present study experimentally investigates indirect interactions arising between two prey species that share a common predator.In a natural field experiment, we introduced different densities of mealworms (Tenebrio molitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Therefore as long as there is a most preferred prey present, then less preferred prey may show little direct predation (e.g. Tschanz et al 2007) and more importantly may also show relatively little decrease in fitness because of their non-lethal compensation.…”
Section: When Less Preferred Prey Have Lower Costs To Reduce Vulnerabmentioning
confidence: 99%
“…Therefore as long as there is a most preferred prey present, then less preferred prey may show little direct predation (e.g. Tschanz et al 2007) and more importantly may also show relatively little decrease in fitness because of their non-lethal compensation.…”
Section: When Less Preferred Prey Have Lower Costs To Reduce Vulnerabmentioning
confidence: 99%
“…While many studies have examined either the predator functional, numerical, or aggregative response in a system (e.g. Colton 1987, Settle et al 1996, Rott et al 1998, Murakami & Nakano 2002, few studies have integrated these responses because of the differences in temporal and spatial scales (Tschanz et al 2007). The functional response operates on a small spatial and temporal scale as it addresses predator feeding in a local prey patch over a short time period.…”
mentioning
confidence: 99%
“…As noted by Schenk and Bacher (2002), the acceleration of the predation rate at low prey densities could be due to the fact that P. dominulus is a generalist predator. Tschanz et al (2007) showed that prey switching between C. rubinigosa and larvae of flour beetles Tenebrio molitor, offered in an experiment as an alternative prey of P. dominulus, could not explain the type-III functional response, but they proposed alternative mechanisms, such as learning or the presence of still another prey than C. rubiginosa and T. molitor.…”
Section: Discussionmentioning
confidence: 99%
“…Although the predator abundance was treated as a constant number across various prey densities, the authors monitored the variations of wasp activity during the day from the video recordings of predation events. We use the latter data and similar observations obtained in later years (Tschanz et al 2007) to fit a gamma distribution in order to establish a predator activity profile during the day (Fig. 1).…”
Section: Experimental Datamentioning
confidence: 99%